Optimalisasi Rute Transportasi pada PT. ABC dengan Metode Nearest Neighbor - Rico Maharandi; Satriardi, Satriardi; Rayendra, Rozar (Fakultas Teknik UMRI, 2025)
PT ABC is a company that provides logistics transportation services for the delivery of various products. PT ABC has a problem, namely that it does not have an optimal route for delivering products. This causes their operational costs to exceed the operational cost standards they set. The Nearest Neighbor method is a method of optimizing operational costs by looking for the shortest point connections to produce the shortest route. After implementing this method, there were route changes, namely for the Long 6 Wheel CDD unit from the initial route G-C1-C2-C3-C4-G it was changed to G-C1-C3-C2-G and for the 6 Wheel CDD unit from the initial route G -C1-C2-C3-C4-G is changed to G-C3-C4-G. Apart from that, there was a reduction in mileage after optimization, namely 269 Km. There is a reduction in operational costs, namely IDR 470,000.